Foreign Illegal, Unreported, and Unregulated Fishing in Somali Waters Perpetuates Conflict - Glaser, Sarah M.; Roberts, Paige M.; Hurlburt, Kaija J. (Frontiers in Marine Science, 2019)
Somali waters have the potential to support some of the most productive fisheries in the world, but the sustainability of those fisheries is compromised by the presence of foreign fishing vessels, many of them fishing illegally. The Somali domestic fishing sector is small and relatively nascent, but foreign vessels have fished in Somali waters for at least seven decades. Some foreign vessels and their crew have been a direct, physical threat to Somali artisanal fishers. Many foreign vessels directly compete for fish, reducing fish populations and destroying marine habitat through bottom trawling. In this paper, we reconstruct foreign catch in Somali waters from 1981 – 2014 and classify the health of seventeen commercial fish stocks. Foreign fishing has increased more than twenty-fold since 1981, and the most rapid increase occurred during the 1990s after the collapse of the Federal government and ensuing civil war. We estimate foreign fishing vessels caught 92,500 mt of fish in 2014, almost twice that caught by the Somali domestic fleet. Iran (48%) and Yemen (31%) accounted for the vast majority of foreign fish catch in the most recent year of analysis. Although responsible for only 6% of total foreign catch, trawl vessels disproportionately impact public perception of foreign fishing. We find they trawled over 120,000 km2 of marine seabed in nearshore waters during 2010 - 2014. Foreign IUU fishing in Somali waters is fueling public anger and perpetuating conflict in five ways: by directly competing with the domestic fishery; through links to piracy; through nearshore illegal and destructive bottom trawling; by contributing to regional political conflict over vessel licensing; and by reducing long-term livelihood security. Significant levels of foreign fishing combined with inconsistent governance means Somalis are not fully benefitting from the exploitation of their marine resources at a local or national level, leading to insecurity at both scales.